Toxicidade aguda da moxidectina em embriões de peixezebra (Danio rerio): bioacumulação e resposta de múltiplos marcadores - Muniz, Marta Silva (2020)
In Brazil, drugs used in cattle have great pollution potential, as the total number of animals exceeds the number of inhabitants. Among these drugs, antiparasitics stand out because they are routinely and prophylactically used in pest control management strategies. In this context, macrocyclic lactones appear as the most important class of antiparasitics worldwide, encompassing two subgroups: avermectins and milbemycins. Although the environmental effects of several avermectins have attracted the attention of researchers, studies on the effects of the main milbemycin (moxidectin) remain scarce. Thus, the present study aimed to elucidate the potential effects of moxidectin in zebrafish embryos (Danio rerio) to provide information on its ecotoxicological profile. For this purpose, we studied the effects of moxidectin through apical endpoints, as well as through enzymatic biomarkers for oxidative stress, xenobiotic processing, anaerobic metabolism, and cholinergic neurotransmission. Moreover, the spatial distribution of moxidectin was determined by means of MALDI-MS imaging, in addition chemical analysis of the embryos and respective exposure solutions. Moxidectin toxicity to zebrafish embryos manifested mainly as a decrease in hatching rates at 96 hpf (EC50 = 18.98 μg/L). It also increased the enzymatic activity of all selected biomarkers and accumulated in the embryos, appearing in concentrations ranging from 0.003-0.03 μM in exposure solutions and from 50-200 μM in embryos. MALDI-MS imaging revealed pockets of the drug mainly in the head and eyes of the embryos (72 and 96 hpf). Thus, our results show that moxidectin causes oxidative stress and a clear pattern of neurotoxicity in early life stages of zebrafish, demonstrating the need to prioritize this compound for environmental studies.